2017
DOI: 10.1016/j.jsps.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Phenylethanoid Glycosides of Cistanche on menopausal syndrome model in mice

Abstract: Cistanche is the traditional and precious Chinese herbal, with two thousand years of use history in China. It has the effect on tonifying kidney, strong supplement to the liver and kidney, and replenishing essence and blood, known as the "desert ginseng". Here, we explored the mechanism of Phenylethanoid Glycosides of Cistanche (PGC) to the model mice of menopausal syndrome, as well as the therapeutic effect and characteristics of PGC to the menopausal syndrome. In this study, KM mice were reproduced by the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…With the increase of the social pressure, the incidence of perimenopausal syndrome also increases and seriously affects women's health, which has become a hot topic in modern medicine (Miao, Tian, Bai, & Xin, 2017). Perimenopausal syndrome, also known as climacteric syndrome, is a syndrome of autonomic nervous system dysfunction disorder caused by ovarian dysfunction and estrogen secretion disorder (Tian, Miao, Bai, & Wei, 2017), accompanied by a series of functional lesions of multiple systems(Zhang, Fu, & Ma, 2015). The main clinical manifestations of perimenopausal syndrome are hot flashes, irritability, insomnia, joint pain, and other conditions caused by low immunity (Scientist, Wadsworth, & Hardy, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of the social pressure, the incidence of perimenopausal syndrome also increases and seriously affects women's health, which has become a hot topic in modern medicine (Miao, Tian, Bai, & Xin, 2017). Perimenopausal syndrome, also known as climacteric syndrome, is a syndrome of autonomic nervous system dysfunction disorder caused by ovarian dysfunction and estrogen secretion disorder (Tian, Miao, Bai, & Wei, 2017), accompanied by a series of functional lesions of multiple systems(Zhang, Fu, & Ma, 2015). The main clinical manifestations of perimenopausal syndrome are hot flashes, irritability, insomnia, joint pain, and other conditions caused by low immunity (Scientist, Wadsworth, & Hardy, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The liver, heart, spleen, thymus, and brain were excised from the mice, and subsequently weighed separately. The thymus and spleen indices were calculated according to the following Formula 1 (Li et al, 2017): For biochemical assays, the organ homogenates, including liver, heart, spleen, and brain, were prepared and centrifuged (4000 rpm/min for 10 min) (Tian et al, 2017). The supernatant was collected for further analysis.…”
Section: Organ Aging Index Determinationmentioning
confidence: 99%
“…In particular, C. deserticola is known as desert ginseng for its nourishing effects [ 21 ]. Several studies reported the chemical components and pharmacological effects of Cistanche species [ 22 , 23 , 24 ]. Previously, we reported the features of four Cistanche plastomes in China, and we found that the Cistanche plastomes were significantly different from those of other angiosperms [ 25 ].…”
Section: Introductionmentioning
confidence: 99%